Aberrant Perfusion of the Serratus Anterior Muscle Flap: Report of Two Cases and a Review of the Literature - BAYRAMİÇLİ, MEHMET NURİ ÜMİT (THIEME MEDICAL PUBL INC, 2010)
Free serratus anterior muscle flap, classified as Mathes-Nahai type III, is a versatile and frequently preferred choice for soft tissue coverage of small to moderate-sized defects owing to its reliable circulation pattern; however, some anatomic variations in the flap vascularity can result in partial flap loss. Here we present two cases with free serratus anterior muscle transfer where the distalmost portion of the flap was not perfused by the thoracodorsal pedicle. The most likely explanation seems to be the large flap size and the lack of distal interconnections between lateral thoracic artery and thoracodorsal artery branches. Our clinical experience suggests that anatomic variations of serratus anterior muscle circulation might end up with distal perfusion loss if a large flap is to be harvested.
Keywords: Serratus anterior; perfusion; muscle flap; variation; ANATOMY; CADAVER; ARTERY